Management Strategies for Dissolved Organic Carbon Reduction from Forested Watersheds using the SWAT-C model. - Lee, Dongjun; Karki, Ritesh; Kalin, Latif; Isik, Sabahattin; Srivastava, Puneet; Zhang, Xuesong (Environmental Management, 2025)
Forests serve as crucial carbon sinks, yet quantifying carbon cycle processes within forested watersheds is challenging due to inherent complexities, including multiple carbon pools and variability. Dissolved organic carbon (DOC) transport from forests significantly impacts drinking water quality since it interacts with chlorine to form disinfection byproducts. Although the Soil and Water Assessment Tool-Carbon (SWAT-C) has been widely used to understand carbon fluxes at the watershed scale, the model has been primarily evaluated in non-forested watersheds and loading to aquatic systems, often overlooking terrestrial carbon fluxes from forested regions within watersheds of interests. This study assessed the applicability of SWAT-C in simulating carbon fluxes in both terrestrial and aquatic systems in the forested Big Creek watershed located in the south-central United States (U.S.), which also serves as a drinking water source, and analyzed dominant pathways of DOC transport across the landscape. Additionally, three management scenarios (i.e., forest conversion, raking in forests, and adjusting biomass harvest in croplands) aimed at reducing DOC transport were evaluated. Calibration efforts using remotely sensed as well as datasets demonstrated the proficiency of SWAT-C in simulating both terrestrial and aquatic carbon fluxes in forest-dominated regions. Results emphasize the importance of initializing and calibrating the parameters of dominant land use/cover types to enhance model performance in simulating carbon fluxes. The study found that all evaluated management scenarios can reduce DOC transport into streams, with the conversion of the dominant loblolly pine forests to restored longleaf pine forests achieving a 40% reduction in forest-derived DOC yields. These findings offer valuable insights for watershed-scale carbon cycling modeling and inform management strategies in forest-dominant watersheds to mitigate DOC yields.